2021
DOI: 10.3390/jpm11050435
|View full text |Cite
|
Sign up to set email alerts
|

Customization of Diet May Promote Exercise and Improve Mental Wellbeing in Mature Adults: The Role of Exercise as a Mediator

Abstract: Diet, dietary practices and exercise are modifiable risk factors for individuals living with mental distress. However, these relationships are intricate and multilayered in such a way that individual factors may influence mental health differently when combined within a pattern. Additionally, two important factors that need to be considered are gender and level of brain maturity. Therefore, it is essential to assess these modifiable risk factors based on gender and age group. The purpose of the study was to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Different physical exercise frequencies are associated with mental distress among men and women before and during the periods of the pandemic, which is a potential proof of concept that customization of physical exercise frequency recommendations is necessary for improving mental wellbeing of men and women. This finding is in line with a previously published report that suggested that customization of dietary and lifestyle factors may be needed to improve mental wellbeing among these cohorts [6]. The lowest probabilities of experiencing mental distress among men and women during the pandemic resulted in differential patterns of physical exercise frequencies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Different physical exercise frequencies are associated with mental distress among men and women before and during the periods of the pandemic, which is a potential proof of concept that customization of physical exercise frequency recommendations is necessary for improving mental wellbeing of men and women. This finding is in line with a previously published report that suggested that customization of dietary and lifestyle factors may be needed to improve mental wellbeing among these cohorts [6]. The lowest probabilities of experiencing mental distress among men and women during the pandemic resulted in differential patterns of physical exercise frequencies.…”
Section: Discussionsupporting
confidence: 91%
“…The benefit of physical exercise on mental health may be through its mediation effect on food. By changing physiological settings, physical exercise might enhance the beneficial effect of nutrient-dense food and reduce the negative impact of low-quality food [6,29].…”
Section: The Modulatory Effect Of Covid-19 On Physical Exercise Frequ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Women are more likely to require a spectrum of nutrient-dense food to achieve mental well-being than men [19], presumably due to the denser connectivity between brain regions [7]. In addition, women's mood appears to be more sensitive to high-glycemic index food and caffeine when compared to men [25]. This could be explained by the different endocrine physiological processes between men and women.…”
Section: Should the Human Brain Be Better Known As The Gender-based B...mentioning
confidence: 99%
“…Most studies combined findings from both men and women and reported an association between diet quality, such as a plant-forward diet, and mental functions. However, studies that investigated the diet based on gender reported differential effects [13,19,25,41]. For instance, a plant-based diet may be more beneficial to women's mood than men's.…”
Section: Bioactive Compounds: a Hidden Potential Brain Remedy?mentioning
confidence: 99%